Vocabulary puzzles : - Molloy, John T. (Wiley Pub., 2007)
Vocabulary Puzzles helps you learn more than 300 key vocabulary words to help you score higher on the SAT, ACT, GRE, LSAT, or other standardized tests. It incorporates a variety of vocabulary-acquisition tools, including crossword puzzles, matching-column exercises, and sample sentence fill-ins. There are even flashcards for all the words so you can review them anytime, anywhere. Based on proven strategies that facilitate learning, this book goes beyond rote memorization for test-taking to help you build a more sophisticated, permanent, and useful vocabulary that will enable you to do well in college, in business, and in life. The goal is to help you own words so you can use them comfortably and confidently.